Analisis Penerapan SAK ETAP dalam Laporan Keuangan Pada Koperasi Unit Desa Kaum Kolot - Widya Prissilia; Irfan Sophan Himawan (Universitas Galuh, 2023)
The presentation of financial statements by accounting standards serves as a benchmark for external parties in evaluating the financial condition of an entity. However, it is currently a fact that the applicable accounting standards are not fully implemented in the process of preparing financial statements. Several cooperatives have been dissolved due to their inability to manage human resources, finances, or operations. This research analyzes the implementation of the Indonesian Financial Accounting Standards for Small and Medium Entities (SAK ETAP) in the preparation of financial statements at the Kaum Kolot Village Cooperative Unit in Jampangkulon District, as well as the competency of the human resources involved in presenting these financial statements. The method used in this research is qualitative, with primary data sources collected through observation, interviews, and documentation. The research findings indicate that the implementation of SAK ETAP in the Kaum Kolot Village Cooperative Unit has been underway, but it is still not fully effective as it only applies to and presents financial statements for the remaining business results, profit and loss, and balance sheet. The competency of the human resources within the Kaum Kolot Village Cooperative Unit is not in line with the required criteria. However, the financial statements produced can provide relevant information that is understandable to the users of the statements.